Safety and efficacy of ultrasound-guided percutaneous A1 pulley release using a needle knife: An anatomical study - Qiu, Zuyun; Li, Hui; Shen, Yifeng; Jia, Yan; Sun, Xiaojie; Zhou, Qiaoyin; Li, Shiliang; Zhang, Weiguang (Frontiers in Surgery, 2022)
Abstract： Objective: The present study aimed to assess the efﬁcacy and safety of ultrasound-guided percutaneous A1 pulley release using a needle knife. Methods: The author performed percutaneous A1 pulley release in 84 cadaveric hands fixed with 10% formalin. The cadaveric hands were divided into three groups: 28 hands in each group (group U: ultrasound-guided needle knife pushing group, group N: non-ultrasound-guided needle knife pushing group, group T: classical needle knife operation puncture group). Percutaneous A1 pulley release was performed, the soft tissue was dissected layer by layer, and the relevant anatomical data were measured. Results：The injured cases were as follows: group U, 29 (20.7%); group N, 36 (25.7%); and group T, 28 (20.0%). There is no significant difference between different tissue injury types in different intervention methods. The missed release cases were as follows: group U, 8 (5.7%); group N, 4 (2.9%); and group T, 13 (9.3%). The percentage of released A1 pulley were as follows: group U, 71.4%±30.7%; group N, 66.0%±20.3%; and group T, 61.00%±30.4%. The percentage of released A1 pulley of the three groups were compared: group U > group N > group T, and there was statistical difference between the three groups. The full release rates of the three groups were compared: group U(31.4%) > group N(15.7%) > group T(13.6%), and there were significant difference in the full release of A1 pulley between group U and group T、group N. Conclusion: Based on the cadaver specimen, the length and percentage of released A1 pulley is longer by ultrasound-guided percutaneous A1 pulley release using a needle-knife. and there was no statistical difference in the injury rate between the three techniques.